Children's rights in health care - Dorscheidt, J. H. H. M., 1964-; Doek, J. E. (Brill Nijhoff, 2018)
While coordinating the University of Groningen's Honours College Winterschool/Atelier entitled Children's Rights in Health Care, the need to publish the contributions to this program was generally expressed and confirmed by its participants. The Winterschool/Atelier, successfully organized in recent years, has dealt with many issues concerning the legal position of minor persons born and unborn in the context of health care, especially pediatric care. These issues involve matters concerning pediatric treatment, preventive care and predictive medicine, medical research involving children, incompetence and child autonomy, a child?s psychological development, parental responsibility and representation, protective judicial measures, child migration issues, children?s health rights enforcement as well as children?s health interest monitoring and promotion. During the program, leading experts in the fields of law, ethics medicine, biology, psychology and institutions such as the Dutch Child & Hospital Foundation, the Child Protection Board, Save the Children, and UNICEF have shared their views on normative standards, practical experiences, significant developments, challenging ideas, silent dreams and inevitable realities. As a result, the Children's Rights in Health Care program provided opportunities for a profound dialogue between Honours College students and lecturing scholars on a wide range of topics involving children?s health care interests. This volume contains several analyses of health rights issues related to children. The various chapters provide an overview of this captivating area and may be of special interest to lawyers, health care professionals, ethicists, psychologists, judicial institutions, policy makers, interest groups, students and all others who are concerned with the children?s rights perspective on health care.